Social media in colorectal surgery. (February 2017) - Wexner, S. D.; Petrucci, A. M.; Brady, R. R.; Ennis‐O'Connor, M.; Fitzgerald, J. E.; Mayol, J.
Abstract: The engagement of social media in healthcare continues to expand. For members of the colorectal community, social media has already made a significant impact on practice, education and patient care. The applications are unique such that they provide a platform for instant communication and information sharing with other users worldwide. The purpose of this article is to provide an overview of how social media has the potential to change clinical practice, training, research and patient care in colorectal surgery.